(untitled) (Revista Cientifica Ingenio Magno, 2022)
The population increase has caused an increase in the emission of methane and carbon dioxide, being gases that cause the negative impact of the greenhouse effect, in greater volume compared to other types of polluting emissions. The increase in organic waste has been detrimental to the environment as it is the main cause of methane gas emissions. On the other hand, one of the great challenges of current engineering is to generate clean energies that meet the different needs of the demand of non-renewable sources of fossil origin, highlighting the use of biogas produced by bacterial anaerobic decomposition. That is why, the present work evidences the second phase of research, which consists of creating a mechanical device for organic waste classification to mitigate the environmental impact in the municipality of Sopó Cundinamarca, for this purpose three moments of organic matter collection are used through an initial filtration, a conveyor belt that will serve as a connecting bridge of an organic waste classification machine at scale using neural networks and image recognition techniques to a selector of organic and inorganic matter that will locate the particles in different places.